The function of nicotinamide phosphoribosyl transferase (NAMPT) and its role in diseases - Peng, Aihong; Li, Junqin; Xing, Jianxiao; Yao, Yuanjun; Niu, Xuping; Zhang, Kaiming (Frontiers in Molecular Biosciences, 2024)
Nicotinamide phosphoribosyl transferase (NAMPT) is a rate-limiting enzyme in the mammalian nicotinamide adenine dinucleotide (NAD) salvage pathway, and plays a vital role in the regulation of cell metabolic activity, reprogramming, aging and apoptosis. NAMPT synthesizes nicotinamide mononucleotide (NMN) through enzymatic action, which is a key protein involved in host defense mechanism and plays an important role in metabolic homeostasis and cell survival. NAMPT is involved in NAD metabolism and maintains intracellular NAD levels. Sirtuins (SIRTs) are a family of nicotinamide adenine dinucleotide (NAD)-dependent histone deacetylases (HDACs), the members are capable of sensing cellular NAD+ levels. NAMPT-NAD and SIRT constitute a powerful anti-stress defense system. In this paper, the structure, biological function and correlation with diseases of NAMPT are introduced, aiming to provide new ideas for the targeted therapy of related diseases.